Obesity Prevention from Conception: A Workshop to Guide the Development of a Pan-Canadian Trial Targeting the Gestational Period. (January 2014) - Adamo, Kristi B.; Shen, Garry X.; Mottola, Michelle; Nascimento, Simony; Jean-Philippe, Sonia; Ferraro, Zachary M.; Nerenberg, Kara; Smith, Graeme; Ohari, Radha; Gaudet, Laura; Piccinini-Vallis, Helena; McDonald, Sarah; et al.
This report summarizes a meeting, Obesity Prevention from Conception, held in Ottawa in 2012. This planning workshop was funded by the Canadian Institutes of Health Research (CIHR) to bring together researchers with expertise in the area of maternal obesity (OB) and weight gain in pregnancy and pregnancy-related disease to attend a one-day workshop and symposium to discuss the development of a cross-Canada lifestyle intervention trial for targeting pregnant women. This future intervention will aim to reduce downstream OB in children through encouraging appropriate weight gain during the mother's pregnancy. The workshop served to (i) inform the development of a lifestyle intervention for women with a high pre-pregnancy body mass index (BMI), (ii) identify site investigators across Canada, and (iii) guide the development of a grant proposal focusing on the health of mom and baby. A brief summary of the presentations as well as the focus groups is presented for use in planning future research.